Hooverville illustration - Thomas Hart Benton (artist):::Creator:::::::::::: (2024)
Hooverville from The Grapes of Wrath, v.2, p.315, illustrated edition by Thomas Hart Benton, a native of eastern Oklahoma, who was assigned to draw archetypal Oklahomans for 20th Century Fox as the studio believed that would make the casting more accurate. "